PENGELOLAAN SAPTA PESONA DI OBJEK WISATA PANTAI PADANG - Heriyantara, Aditia; Kasmita, Kasmita; Waryono, Waryono (Journal of Home Economics and Tourism, 2015)
As for the purpose of this study was to describe: (a) planning, (b) organization, (c) direction, and (d) supervision in Sapta Pesona Beach Attractions Padang. Type of research is qualitative research. As for the research question is how management stepping in attraction Padang beach. Data collection techniques performed by using interviews, observation and documentation involving, namely: managers of attractions, attractions surrounding communities. The data analyzed include three grooves activities namely, data reduction, data presentation, and making conclusions. Based on the results of the study found some issues related to the management of stepping in Padang beach a tourist attraction, namely: 1) planning, 2) organizing 3) directing, and 4) supervision attraction patai Padang. Planning related to the objectives to be achieved in the long term, namely the sustainability of the coast of Padang as maritime tourist attraction and in the short term as a growing attraction. Plan implementation is done by means of securing and optimizing existing security officer attractions. Reporting is done verbally from the clerk to the coordinator for operations, while reporting administratively done in writing. Briefing conducted by reminding each other by management personnel attractions of the tasks to be done. Supervisors do managers together with the community, police, municipal police, the Department of Health Taman Padang.